Modulation of Fusicoccin-Binding Protein Activity in Mung Bean (Vigna radiata L.) Hypocotyls by Tissue Maturation and by Fusicoccin. - Basel, L. E. (1994)
The phytotoxin fusicoccin (FC), after binding to a plasma membrane-localized receptor, causes higher plant cells to excrete protons. Ligand-binding analysis has been used to show that the plasma membrane of mung bean (Vigna radiata L.) hypocotyls contains both high-affinity (HA) and low-affinity (LA) binding sites for FC. The effect of tissue maturation on these sites was determined on isolated membrane vesicles from the meristematic region (hook) and the elongation zone and from mature hypocotyl tissues. In the meristematic region the HA:LA ratio was 1:20. As hypocotyl tissues matured, the site density of HA increased and there was no change in LA density, so that the HA:LA ratio increased to 1:2 in maturet issues. FC-induced proton excretion correlates with the HA density, not the LA density. When sections isolated from each region were incubated with FC prior to isolation of membranes, there was an apparent conversion of LA to HA sites during the first 90 min in all regions. During the next 1 to 3 h there was a further 2.5- to 3- fold increase in binding sites in all regions, accompanied by a slight decline in dissociation constant. The increase in binding sites, but not the apparent conversion of LA to HA, was partly blocked by cycloheximide. These data suggest that FC alters FC-binding protein activity in two ways: first, by causing an increase in affinity for FC of preexisting LA receptors, and second by inducing the synthesis of additional FC receptors. This apparent up-regulation of a phytotoxin receptor by its ligand in plants has not previously been reported.